(untitled) (Anwer Khan Modern Medical College Journal, 2022)
Background and objectives: Basic components for Intra-cardiac repair of TOF are the same in every cardiac center except the timing which varies according to the capability of the team. Free PR is inevitable in case of a trans-annular patch which ultimately leads to RV dilatation, dysfunction, arrhythmia and failure with time. There is an ongoing endeavor to reconstruct the RVOT with the aim to avoid free PR in physiological repair. If RVOT reconstruction is done, RV dysfunction is absent or delayed which can avoid further re intervention. Monocuspid reconstruction of PV is commonly practiced in many centers but its long term outcome is poor though it helps to achieve aless stormy ICU course. Modified monocusp or bicuspid PV reconstruction is adopted in many centers using 0.1mm PTFE membrane. We represented the results of Modified Monocus PV reconstruction using a 0.1mm PTFE patch in repair of TOF with a trans-annular patch. Methodology: A total, 42 patients diagnosed as TOF were treated from January 2016 to October 2020. Age ranged from 18 months to 35 years, weighing 10 kg to 70 kg. 38 patients had TOF and 4 had DORV with PS. The trans-annular patch was followed by implantation of a 0.1-mm PTFE valve using posterior fixation. Results: Among the total42 patients,28 were male and 14 were females. Mean age was10.51±7.49 yrs and BSA was 0.90±0.34 kg/m2. Mean total bypass time was 187±31 min, cross-clamp time was 123.63±25.42 min. Out of 42 patients, 9(21.43%) had a PV gradient 0-10 mm/Hg, 24(57.14%) had 10-20 mm/Hg, and 9(21.43%) had >20 mm/Hg in the post-operative echocardiogram. PR gradient was trivial in 7(16.67%), mild in 31(73.1%), moderate in 4(9.52%) patients. Follow-up echocardiogram revealed PR gradient remained trivial in 4(10%) patients, augmented from trivial to mild in 3(7.5%) and mild to moderate in 05(12.5%) patients. It remained moderate in 03(7.5%). There was no severe PR. ICU stay was 89±32.6 hours and mean hospital stay 11.48±2.1 days. Conclusions: Initial results using a transannular patch with a modified monocuspvalve to repair the RV outflow tract in cases of tetralogy of Fallot were promising. There were only a slight pressure gradient and mild regurgitation in most of the cases. A medium or long-term follow-up study is required to confirm these findings and compare them with results obtained using other techniques. AKMMC J 2021; 12(2): 82-90